2016
DOI: 10.7554/elife.17551
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin signaling regulates nephron segment patterning of renal progenitors during zebrafish kidney development

Abstract: Kidney formation involves patterning events that induce renal progenitors to form nephrons with an intricate composition of multiple segments. Here, we performed a chemical genetic screen using zebrafish and discovered that prostaglandins, lipid mediators involved in many physiological functions, influenced pronephros segmentation. Modulating levels of prostaglandin E2 (PGE2) or PGB2 restricted distal segment formation and expanded a proximal segment lineage. Perturbation of prostaglandin synthesis by manipula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
85
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(89 citation statements)
references
References 64 publications
3
85
0
Order By: Relevance
“…During zebrafish embryogenesis, mesenchymal renal progenitors undergo an epithelial transition to form initially linear pronephric tubules by 24 hpf (Gerlach and Wingert, 2014; McKee et al, 2014). Thus, we used a riboprobe to label cells expressing cdh17 , which is expressed throughout the tubule and duct of the pronephros at 24 hpf, along with a ribroprobe designed to detect wt1b transcripts, to label podocytes, and then measured absolute tubule length from the rostral to caudal extent (Poureetezadi et al, 2016). Compared to WT embryos, the zep-/- developed tubules that were statistically the same length, while they lacked bilateral clusters of wt1b+ expressing cells as we had observed previously (Figure 3A,B).…”
Section: Resultsmentioning
confidence: 99%
“…During zebrafish embryogenesis, mesenchymal renal progenitors undergo an epithelial transition to form initially linear pronephric tubules by 24 hpf (Gerlach and Wingert, 2014; McKee et al, 2014). Thus, we used a riboprobe to label cells expressing cdh17 , which is expressed throughout the tubule and duct of the pronephros at 24 hpf, along with a ribroprobe designed to detect wt1b transcripts, to label podocytes, and then measured absolute tubule length from the rostral to caudal extent (Poureetezadi et al, 2016). Compared to WT embryos, the zep-/- developed tubules that were statistically the same length, while they lacked bilateral clusters of wt1b+ expressing cells as we had observed previously (Figure 3A,B).…”
Section: Resultsmentioning
confidence: 99%
“…It is commonly recognized that COX-1 serves a constitutive housekeeping role [ 18 ]. Evidence has shown that COX-1 could regulate nephron formation via PGE2 in the zebrafish embryonic kidney [ 19 ]. COX-1 is also responsible for maintaining basic physiological functions including cytoprotection of the gastric mucosa and platelet aggregation [ 20 , 21 ].…”
Section: Cox S In Kidney Diseasesmentioning
confidence: 99%
“…Additionally, genetic studies in zebrafish are readily performed using reverse approaches like genome editing, knockdown or various overexpression techniques, as well as forward approaches like chemical genetics. Recently, we reported the results from a novel small molecule screen using the zebrafish pronephros as a segmentation model, which included the discovery that modulators of peroxisome proliferator-activated receptor (PPAR) signaling altered nephron segmentation ( Poureetezadi et al, 2016 ). Until the present study, however, the functions of discrete PPAR signaling components during nephrogenesis have remained unknown.…”
Section: Introductionmentioning
confidence: 99%
“… Nephron segmentation involves a concert of genetic and molecular signals that are not fully understood. Through a chemical screen, we discovered that alteration of peroxisome proliferator-activated receptor (PPAR) signaling disrupts nephron segmentation in the zebrafish embryonic kidney ( Poureetezadi et al, 2016 ). Here, we show that the PPAR co-activator ppargc1a directs renal progenitor fate.…”
mentioning
confidence: 99%